BALOs Improved Gut Microbiota Health in Postlarval Shrimp (Litopenaeus vannamei) After Being Subjected to Salinity Reduction Treatment - Cao, Qingqing; Najnine, Farhana; Han, Hongcao; Wu, Bing; Cai, Junpeng (Frontiers in Microbiology, 2020)
White shrimp, Litopenaeus vannamei, is a widely farmed species. In China, shrimp postlarvae (PL) are frequently subjected to salinity reduction treatment to meet end growers’ needs. However, while this treatment effectively reduces vibrio counts, its impact on gut microbiota health is still unknown. In this study, we applied a euryhaline strain of BALOs, BDN-1F2 (BD), and Bacillus subtilis (SD) to the rearing of second generation shrimp PL after salinity reduction treatment, so as to determine if they could impact PL gut microbiota by using high throughput sequencing analysis. Results showed that PL gut microbiota, both compositionally and functionally, have been badly wrecked after salinity reduction treatment, with the generally-recognized-as-opportunistic-pathogens Gammaproteobacteria being the only dominant class at day 1 of test, viz., 99.43%, 85.61% and 83.28% in BD, SD and control (CD) groups, respectively. At day 7, Gammaproteobacteria was still the only dominant class in SD and CD groups, with relative abundance of 99.77% and 99.87% correspondingly, whereas in BD group, its value dropped to 8.44%. Regarding biodiversity parameter the Shannon index, over the 7-day test period, while SD group was unchanged (0.98 to 0.93), CD group dropped to 0.94 from 2.94, and BD group raised to 7.14 from 0.93. Functionally, compared to control, SD group displayed similar strength of various predicted community functions, but BD group had hugely enhanced its various capabilities (p < 0.05). These results demonstrated that addition of BDN-1F2 had exceedingly improved PL gut microbiota health by raising its biodiversities and strengthening its functionalities. On reviewing data derived from this as well as relevant studies, a Shannon index cut-off value was tentatively suggested so as to differentiate microbiota-healthy PL7-15 from the unhealthy ones. Furthermore, a conceptual mechanism of BALOs in the rectification/improvement of a microbial community health has also been proposed.